Creative computing and the generative artist. (2016) - Battey, Bret
This article addresses the research agenda of creative computing from the perspective of a generative artist/composer, someone for whom processes of software creation and art creation inseparably intertwine. Using his audiovisual composition Clonal Colonies (2011) as a case study, the author addresses the dynamic of generative artistic creation when it is a process of discovery and dialog with artist-created, often unpredictable software systems. He provides technical specifics regarding his use of his variable-coupled map networks approach for music and his Brownian Doughnut Warper visual algorithm. Finally, he proposes a set of principles applicable to the creation of generative artwork, considers how tools and systems could better support such work, and proposes that creative computing research also focus on helping creatives surmount the fundamental personal challenges encountered in creative work of all types.